2022
DOI: 10.3390/children9071082
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Machine Learning Classifiers in Classifying Stunting among Under-Five Children in Zambia

Abstract: Stunting is a global public health issue. We sought to train and evaluate machine learning (ML) classification algorithms on the Zambia Demographic Health Survey (ZDHS) dataset to predict stunting among children under the age of five in Zambia. We applied Logistic regression (LR), Random Forest (RF), SV classification (SVC), XG Boost (XgB) and Naïve Bayes (NB) algorithms to predict the probability of stunting among children under five years of age, on the 2018 ZDHS dataset. We calibrated predicted probabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…They achieved the maximum accuracy of 87.7% for wasted, 88.3% for stunted, and 85.7% for underweight, obtained by the RF algorithm. Random Forest performed better than other algorithms in Chilyabanyama's research on predicting stunting among children under five in Zambia, which supports the current investigation's findings [49].…”
Section: Plos Onesupporting
confidence: 86%
“…They achieved the maximum accuracy of 87.7% for wasted, 88.3% for stunted, and 85.7% for underweight, obtained by the RF algorithm. Random Forest performed better than other algorithms in Chilyabanyama's research on predicting stunting among children under five in Zambia, which supports the current investigation's findings [49].…”
Section: Plos Onesupporting
confidence: 86%
“…SVM is a set of supervised learning methods used for classification, regression, and outlier detection. SVMs are preferred when dealing with high-dimensional spaces, robustness to outliers, nonlinearity, margin maximization, memory efficiency, and small to medium-sized datasets are important considerations for the problem at hand 42 . However, SVMs may have limitations in terms of scalability to large datasets and computational efficiency, especially when using non-linear kernels.…”
Section: Methodsmentioning
confidence: 99%
“…LR is a supervised ML algorithm used to solve classification issues. It is a parametric method that assumes a Bernoulli distribution of the target variable and the independence of the observations 42 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study that evaluated the performance of machine learning classifiers in predicting stunting among children under five in Zambia. The study found that the random forest classifier outperformed other classifiers in terms of accuracy, sensitivity, and specificity (Chilyabanyama et al, 2022).…”
Section: A Introductionmentioning
confidence: 92%